3D-Printed Bowtie Filter Created by High Precision NanoJet System Combined with Novel Printing Strategy - Sippel, Mark; Lomakin, Konstantin; Ankenbrand, Markus; Petersen, Matthias; Franke, Jörg; Helmreich, Klaus; Vossiek, Martin; Gold, Gerald (28th Conference on Electrical Performance of Electronic Packages and Systems (EPEPS 2019), 2019)
This paper focuses on the latest aerosol based printing system in conjunction with a newly developed manufacturing method. The presented novel method is successfully demonstrated on a Bowtie Filter in comparison to the same pho-tolithographically produced structure.<br

Analysis of the Suitability of Inkjet-Printed Ag-Particle-Filled Inks for Use in Connections of Fine-Pitch Electrical Components - Voigt, Christian; Petersen, Matthias; Thielen, Nils; Utsch, Daniel; Häußler, Felix; Kirchberger, Manfred; Franke, Jörg (2023 46th International Spring Seminar on Electronics Technology (ISSE), 2023)
This paper explores a method for contacting Surface Mount Devices (SMD) using inkjet-printed media. A series of experiments is conducted to determine the needed layer thickness, drop size, and print parameters to facilitate adequate connections and evaluates the mechanical forces needed to break such a connection. Analysis of the joining partners using laser scan microscopy indicates necessary ink volumes between 75.1*10 3 and 800*10 3 μm 3 of connective media depending on the SMD size. The necessary amount of material is delivered to the substrate surface using inkjet printing, with the appropriate dwell voltage being determined in a separate experiment. After sintering for 10 minutes at 150°C, the inkjet-printed connections demonstrated electrical conduction in testing but showed 43% less resistance to shear forces, when compared to conventionally soldered connections, indicating a need for further optimization regarding the adhesive properties of the ink. The study provides insights for developing mechanically and electrically stable connections using inkjet-printed media, although further refinement is needed with regards to ink formulation and sintering tim

Atmospheric Plasma Spraying for Copper Coating of Ceramic Solid Electrolytes for Anode-Free Solid-State Batteries with Increased Interfacial Contact - Ockel, Manuela; Borchers, Andre; Fröhlich, Jan; Petersen, Matthias; Paschen, Timo; Christiansen, Silke; Franke, Jörg (2024 1st International Conference on Production Technologies and Systems for E-Mobility (EPTS), 2024)
Advances in solid-state battery technology are crucial for future energy storage solutions. Atmospheric plasma spraying (APS) offers a novel approach for producing copper coatings on ceramic solid electrolytes (SE) for anode-free solid-state batteries (AFSSBs), which generally promise increased safety and energy density. This study investigates the feasibility of APS for the fabrication of Cu-based current collectors with enhanced interfacial contact at the SE and high material deposition rates in comparison to physical or chemical vapor deposition of Cu. The qualitative results suggest that APS can produce Cu coatings with high interfacial contact without inducing high pressures through calendaring, which can lead to cracks in brittle solid electrolytes. This research addresses critical challenges in the production of AFSSBs with APS and evaluates the importance of tailored interface properties for optimized contact areas. The pressure induced by the accelerated particles is substantially lower compared to conventional calendaring tools. Surface characteristics of SE and coating were analyzed via laser scanning. SEM analysis showed several defects during splat formation, which reduces interfacial contact.<br

Cold Atmospheric Plasma Metallization of Power Semiconductor Bare Dies with CuSn Pseudo-Alloys for Diffusion Soldering - Ockel, Manuela; Gökçen, Aleyna; Ottinger, Bettina; Petersen, Matthias; Voigt, Christian; Franke, Jörg (ITSC 2024 International Thermal Spray Conference and Exposition. Conference Proceedings and Poster Sessions, 2024)

Evaluation and Characterization of 3D Printed Pyramid Horn Antennas utilizing different Deposition Techniques for Conductive Material - Lomakin, Konstantin; Pavlenko, Tatiana; Ankenbrand, Markus; Sippel, Mark; Ringel, Johannes; Scheetz, Matthias; Klemm, Tobias; Gräf, Daniel; Helmreich, Klaus; Franke, Jörg; Gold, Gerald (IEEE Transactions on Components, Packaging and Manufacturing Technology, 2018)
This paper evaluates different metal deposition approaches for a two-staged additive manufacturing (AM) process for 3-D horn antennas, divided into the deposition of plastic and conductive material. The demonstrated fabrication workflow allows for antennas of low cost and low weight and, therefore, demonstrates the vast benefit of AM. The comparison of a commercially available cast aluminum horn to the fabricated prototypes reveals a deviation of up to 3 dB in terms of transmission losses in copolarization over a distance of 1.85 m. Cross-polarization measurements are presented revealing a larger variation among the different metallization approaches. The results shown in this paper demonstrate a successful application of AM in radio frequency engineering. Moreover, one of the presented approaches makes use of only 3-D printing systems and is, therefore, potentially suitable for totally automated manufacturin
lhft_intern.bib::Lomakin2018g

Generation of 3D Functional Structures for High- Frequency Applications by Printing Technologies - Ankenbrand, Markus; Scheetz, Matthias; Franke, Jörg; Lomakin, Konstantin; Sippel, Mark; Gold, Gerald; Helmreich, Klaus (2018 13th International Congress Molded Interconnect Devices (MID), 2018)
The following topics are dealt with: polymers; adhesion; rapid prototyping (industrial); mechatronics; aerosols; injection moulding; moulding; three-dimensional printing; metallisation; electrical resistivit

Investigations of Silver Sintered Interconnections 3-Dimensional Ceramics with Plasma Based Additive Copper Metallizations - Hensel, Alexander; Schwarzer, Christian; Scheetz, Matthias; Kaloudis, Michael; Franke, Jörg (2018 IEEE 20TH ELECTRONICS PACKAGING TECHNOLOGY CONFERENCE (EPTC), 2018)
CRIS-Team WoS Importer:2019-04-12

Pushing the Boundaries of 3D-MID: Pulse-Width Modulated Light Technology for Enhancing Surface Properties and Enabling Printed Electronics on FFF-Printed Structures - Gräf, Daniel; Neermann, Simone; Stuber, Lisa; Scheetz, Matthias; Franke, Jörg (2018 13th International Congress Molded Interconnect Devices (MID), 2018)
Keywords: aerosols; ink; light sources; mechatronics; nanoparticles; polymers; rapid prototyping (industrial); silver; sintering; surface roughness; surface treatment; three-dimensional printing; xenon; light sintering; pulse-width modulated light technology; printed electronics; fused filament fabrication; aerosol-jet printing system; 3D-MID; surface roughness; heat sensitive materials; polylactic acid; surface treatment; silver nanoparticle ink; Ag; Surface treatment; Rough surfaces; Surface roughness; Printing; Field-flow fractionation; Ink; Silver; Additive Manufacturing; Printed Electronics; Fused Filament Fabrication; Surface Treatment; Silver Nanoparticle Ink; Aerosol-Jet Printing; Pulse-Width Modulated Light Technology; Sintering Process

Substrate pretreatments: an investigation of the effects on aerosol jet printed structures - Neermann, Simone; Scheetz, Matthias; Franke, Jörg; Roudenko, Jewgeni; Schirmer, Julian; Reichenberger, Marcus (WGP-Jahreskongress, 2018)